(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
The article focuses on the international traffic of Italian hazardous waste directed to Nigeria between 1987 and 1988. In particular it analyses the Italian-Nigerian route, which was the one most used by the companies that organized and carried out the traffic during the 1980s, the actors who took part in it, the goods that were unloaded and the important - and so far scarcely explored - effects on the bilateral relations between Italy and Nigeria.